Haemoglobin changes and risk of anaemia following treatment for uncomplicated falciparum malaria in sub-Saharan Africa - Zwang, J; D'Alessandro, U; Ndiaye, J; Djimdé, A; Dorsey, G; Mårtensson, A; Karema, C; Olliaro, P (BioMed Central, 2017)
Background Anaemia is common in malaria. It is important to quantitate the risk of anaemia and to distinguish factors related to the natural history of disease from potential drug toxicity. Methods Individual-patient data analysis based on nine randomized controlled trials of treatments of uncomplicated falciparum malaria from 13 sub-Saharan African countries. Risk factors for reduced haemoglobin (Hb) concentrations and anaemia on presentation and after treatment were analysed using mixed effect models. Results Eight thousand eight hundred ninety-seven patients (77.0% <5 years-old) followed-up through 28 days treated with artemisinin combination therapy (ACT, 90%, n = 7968) or non-ACT. At baseline, under 5’s had the highest risk of anaemia (77.6% vs. 32.8%) and higher parasitaemia (43,938 μl) than older subjects (2784 μl). Baseline anaemia increased the risk of parasitological recurrence. Hb began to fall after treatment start. In under 5’s the estimated nadir was ~35 h (range 29–48), with a drop of −12.8% from baseline (from 9.8 g/dl to 8.7 g/dl, p = 0.001); in under 15’s, the mean Hb decline between day 0–3 was −4.7% (from 9.4 to 9.0 g/dl, p = 0.001). The degree of Hb loss was greater in patients with high pre-treatment Hb and parasitaemia and with slower parasite reduction rates, and was unrelated to age. Subsequently, Hb increased linearly (+0.6%/day) until day 28, to reach +13.8% compared to baseline. Severe anaemia (<5 g/dl, 2 per 1000 patients) was transient and all patients recovered after day 14, except one case of very severe anaemia associated with parasite recurrence at day 28. There was no systematic difference in Hb concentrations between treatments and no case of delayed anaemia. Conclusion On presentation with acute malaria young children with high parasitaemia have the highest risk of anaemia. The majority of patients experience a drop in Hb while on treatment as early as day 1–2, followed by a linear increase through follow-up. The degree of the early Hb dip is determined by pre-treatment parasitaemia and parasite clearance rates. Hb trends and rick of anaemia are independent of treatment.